Discriminating from species of Curcumae Radix (Yujin) by a UHPLC/Q-TOFMS-based metabolomics approach. Issue 1 (December 2016) - Liu, Fang; Bai, Xu; Yang, Feng-Qing; Zhang, Xiao-Jing; Hu, Yuanjia; Li, Peng; Wan, Jian-Bo
Abstract Background Chinese medicinal herbs may use more than one species ofCurcumae Radix (Yujin ) is the tuberous roots ofCurcumae wenyujin, C. kwangsiensis, C. phaeocaulis andC. longa . This study aimed to characterize the chemical profiles of these different species ofCurcumae Radix, and develop a method for rapid discrimination of these species by ultra-high performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UHPLC/Q-TOFMS) combined with multivariate statistical analysis. Methods The metabolomes of 33 different batches ofCurcumae Radix derived from fourCurcumae species were profiled by UHPLC/Q-TOFMS. The resulting sample codes, t R –m/z pairs and ion intensities were processed by unsupervised principal component analysis (PCA) and supervised orthogonal partial least squared discriminant analysis (OPLS-DA) to characterize the chemical composition ofCurcumae Radix across the four different species. Results Obvious differences were observed in the chemical compositions of theCurcumae Radix samples derived from the four different species according to PCA and OPLS-DA. These results suggested that curcumin, curcumenone, curcumenol and zederone could be used as unique chemical markers forC. longa, C. wenyujin, C. phaeocaulis and C.kwangsiensis, respectively. Conclusions This study developed a UHPLC/Q-TOFMS method coupled with multivariate statistical analysis to discriminate betweenCurcumae Radix samples from four differentCurcumae species, i.e., C. longa, C. wenyujin, C. phaeocaulis andC. kwangsiensis . Notably, this new approach resulted in the identification of curcumin (a ), curcumenone (b ), curcumenol (c ) and zederone (d ) as unique chemical markers for the identification.